To rewrite the expression \( 2712 \cdot 2714 \), we can use the properties of exponents. We can combine the terms as follows:
\[ 2712 \cdot 2714 = 27^{12} \cdot 27^{14} = 27^{12 + 14} = 27^{26} \]
Now, leaving the expression \( 2712 \cdot 2714 \) as \( 27^{26} \) in simplified exponential form.
If you are looking for a form involving roots (like your given options), we can rewrite \( 27^{26} \) in terms of roots and fractions:
- \( 27^{26} = \sqrt[4]{27^4}^{26} = 27^{4 \cdot 6.5} = (27^{4})^{6.5}\)
- Or in fractional exponents: \[ 27^{26} = 27^{(1/8) \cdot 208} = (27^{1/8})^{208} \] Here, you will notice it's not a straightforward simplification to align with your given options.
Depending on the context of your choices, it's best to follow the specific expression or outputs you are provided with. However, the clearer exponent-based form from your operation is \( 27^{26} \).
If you need a conversion into roots, you could express it in a way like \[ 27^{26} = (27^{1/4})^{104} = \sqrt[4]{27^{104}} \] But this might not be directly among your options, and without clear connection, it’s critical to derive the precise expectation from your requirements.
Please let me know if there's more context or specific interpretations you want for the result!